Effect of the 1983 Mental Health Act on the management of psychiatric patients. Issue 6612 (12th December 1987) - Webster, L; Dean, C; Kessel, N
Abstract : Two principal objectives of the 1983 Mental Health Act were to decrease the use of emergency orders and to give patients on observation orders the right of appeal. Statistics were collected from the 13 hospitals that admit acute psychiatric patients in the Greater Manchester area, and the figures for 1980-1 were compared with those for 1984-5. Changes in use of the different sections were examined in university units, large psychiatric hospitals, and district general hospital units. The use of emergency orders decreased and the use of treatment orders increased; the use of observation orders remained unchanged. Many more patients exercised their right of appeal in 1984-5, but the number discharged by tribunals remained small. The nurses' holding power was used infrequently. The different types of hospital are now more concordant in their use of these orders than before the 1983 act.